Shuttling single metal atom into and out of a metal nanoparticle. Issue 1 (December 2017) - Wang, Shuxin; Abroshan, Hadi; Liu, Chong; Luo, Tian-Yi; Zhu, Manzhou; Kim, Hyung; Rosi, Nathaniel; Jin, Rongchao
Abstract It has long been a challenge to dope metal nanoparticles with a specific number of heterometal atoms at specific positions. This becomes even more challenging if the heterometal belongs to the same group as the host metal because of the high tendency of forming a distribution of alloy nanoparticles with different numbers of dopants due to the similarities of metals in outmost electron configuration. Herein we report a new strategy for shuttling a single Ag or Cu atom into a centrally hollow, rod-shaped Au24 nanoparticle, forming AgAu24 and CuAu24 nanoparticles in a highly controllable manner. Through a combined approach of experiment and theory, we explain the shuttling pathways of single dopants into and out of the nanoparticles. This study shows that the single dopant is shuttled into the hollow Au24 nanoparticle either through the apex or side entry, while shuttling a metal atom out of the Au25 to form the Au24 nanoparticle occurs mainly through the side entry. Doping a metal nanocluster with heteroatoms dramatically changes its properties, but it remains difficult to dope with single-atom control. Here, the authors devise a strategy to dope single atoms of Ag or Cu into hollow Au nanoclusters, creating precise alloy nanoparticles atom-by-atom.